Modern American painting - Time-Life Books ([Netherlands] Time-Life International, 1970)
Traces the changes and developments in American art in the twentieth century, discussing such artists as Pollock, Sloan, Glackens, Bellows, O'Keeffe, Warhol, Gorky and others.
Ash can school -- Impact of abstraction -- America rediscovered -- Social realists -- Debt to Europe -- Birth of a native style -- Soup can school.
Includes bibliographical reference (page 187) and index.
Keywords: Painting, American; Painting, Modern -- 20th century -- United States